Implementation of Hybrid Contracts in the Gold Pawn Practice in Sharia Pawnshops - Dimas Kenn Syahrir; Erika Amelia (Universitas Wahid Hasyim Semarang, 2023)
The hybrid contract in sharia pawn practice is very unique. This gives rise to different views on the transaction model. Several contracts are often applied in hybrid contract of sharia pawn practice include qardh, rahn, and ijarah. In an ijarah contract of sharia pawn, there is indication of irrelevance in the calculation of ujrah from the clause of the fatwa No.25/DSN-MUI/III/2002 concerning Rahn. This research intends to examine the implementation of hybrid contract in sharia pawn practices by raising the case of gold pawn referring to clause of the fatwa. This study applies a qualitative research paradigm with data characteristics consisting of concepts and qualitative statements. The sources of data were obtained from the implementation of sharia pawn practice in several sharia financial institutions and pawnshop companies, contract concepts, and DSN MUI fatwas. From this study, it was found that the rahn and qardh contracts in Islamic pawnshops complied with the clause of the DSN fatwa No.26/DSN-MUI/III/2002 concerning gold rahn. However, there is a potential for riba practices in ijarah contract in sharia pawn that conflict with the DSN fatwa No.25/DSN-MUI/III/2002 concerning Rahn. The potential for riba is indicated from the calculation of ujrah based on the amount of loans.AbstrakKontrak gadai multi akad dalam pegadaian syariah memiliki sisi keunikan. Hal itu menimbulkan berbagai pandangan mengenai model transaksi tersebut. Beberapa akad yang sering diterapkan dalam multi akad dalam pegadaian syariah antara lain akad qardh, rahn, dan ijarah. Dalam akad ijarah dari pegadaian syariah, terdapat indikasi adanya penyimpangan perhitungan ujrah dari ketentuan fatwa DSN No.25/DSN-MUI/III/2002 tentang Rahn. Penelitian ini hendak menelaah implementasi multi akad dalam praktik gadai syariah dengan mengangkat kasus gadai emas mengacu pada ketentuan fatwa tersebut. Penelitian ini menggunakan paradigma penelitian kualitatif dengan karakteristik datanya terdiri dari konsep dan pernyataan kualitatif. Sumber data diperoleh dari implementasi gadai di pegadaian syariah di beberapa lembaga keuangan syariah dan perusahaan pegadaian, konsep-konsep akad, dan fatwa-fatwa DSN MUI. Dari penelitian ini, ditemukan bahwa akad rahn dan qardh dalam pegadaian syariah telah sesuai dengan ketentuan fatwa DSN No.26/DSN-MUI/III/2002 tentang rahn emas. Akan tetapi, terdapat potensi praktik riba dalam akad ijarah dalam pegadaian syariah yang bertentangan dengan fatwa DSN No.25/DSN-MUI/III/2002 tentang Rahn. Potensi riba ini tampak pada perhitungan ujrah berdasarkan besarnya pinjaman.